The Use of E-Marketing Tools as Marketing Efforts For MSME Products In Hariara Pohan Tourist Village, Samosir Regency, North Sumatra Province: Penggunaan E-Marketing Dalam Upaya Pemasaran Produk Umkm di Desa Wisata Hariara Pohan, Kabupaten Samosir, Sumatera Utara - Sinaga, Deafani Clara; Marpaung, Hasoloan; Sitompul, Sumihar Sebastiana (LPPM Institut Pendidikan Nusantara Global, 2024)
Holbung Hill is one of the more fascinating tourist destinations in Samosir Regency, North Sumatra and located in Hariara Pohan Tourist Village. This Village has several village mainstay products, or Micro, Small, and Medium Enterprises (MSME) products, which are made directly by the local community and then used as souvenirs typical of Hariara Pohan Village. These products are Sasagun Snack (rice flour mixed with coconut and then roasted with brown sugar or just simple white sugar), Tipa-tipa Snack (Comes from young rice seeds, known as a typical Batak cereal), dodol sticky rice, and Bandrek Mallatam. These MSME products are still infrequently promoted through digital media (e-marketing). Researchers are interested in conducting a study and finding the obstacles or causes of Hariara Pohan Tourism Village MSME product underpromotion on social media accounts in Hariara Pohan Village, Samosir Regency. This research method uses a qualitative research and data was collected through direct interviews and observation with MSME actors, local communities, and Hariara Pohan Village administrators and officials. The result of this research is the obstacles faced by the local communities as MSME actors in Hariara Pohan Village in using e-marketing as a marketing medium are due to several things, such as: lacking of digital skills and human resources, minimal understanding of technology, limited budget for marketing, limitations access to the internet, local communites are still lacking in understanding the target market